2018
DOI: 10.1159/000486718
|View full text |Cite
|
Sign up to set email alerts
|

Association between Antioxidant Enzyme Activities and <b><i>Enterovirus</i></b>-Infected Type 1 Diabetic Children

Abstract: Significance of the Study• This study revealed that children with type 1 diabetes (T1D) infected with Enterovirus (EV) show a marked decrease in glutathione peroxidase, superoxide dismutase, and catalase activity, and a noticeable elevation in C-reactive protein compared to noninfected diabetic children. Our results confirm an association of EV infection with the inflammation and β cell damage seen in T1D, and suggest that antioxidant supplementation can play a protective role. DOI: 10.1159/000486718Keywords T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
2
0
9
Order By: Relevance
“…ОС характеризуется дисбалансом между образованием и деградацией активных форм кислорода (АФК) или активных форм азота (АФА) и сниженным уровнем антиоксидантов, вызывающих патологический эффект на работу клеточных механизмов [14][15][16][17][18]. Этот эффект может быть опосредован генетическим недостатком антиоксидантных ферментов, а также факторами окружающей среды (например, вирусные инфекции) [6]. Другими словами, ОС развивается, когда скорость образования свободных радикалов (СР) превышает возможности систем антиоксидантной защиты организма, что приводит к токсическому воздействию СР на клетки [12,19].…”
Section: оксидативный стресс: основные патофизиологические звеньяunclassified
See 3 more Smart Citations
“…ОС характеризуется дисбалансом между образованием и деградацией активных форм кислорода (АФК) или активных форм азота (АФА) и сниженным уровнем антиоксидантов, вызывающих патологический эффект на работу клеточных механизмов [14][15][16][17][18]. Этот эффект может быть опосредован генетическим недостатком антиоксидантных ферментов, а также факторами окружающей среды (например, вирусные инфекции) [6]. Другими словами, ОС развивается, когда скорость образования свободных радикалов (СР) превышает возможности систем антиоксидантной защиты организма, что приводит к токсическому воздействию СР на клетки [12,19].…”
Section: оксидативный стресс: основные патофизиологические звеньяunclassified
“…Антиоксидантная система состоит из ферментативных и неферментативных антиоксидантов [16]. Антиоксидантные ферменты включают: супероксиддисмутазу, глутатионпероксидазу и каталазу и другие ферменты, которые могут катализировать деградацию АФК/АФА [6,16]. Неферментативные антиоксиданты включают: глутатион, полиамин и билирубин, которые могут непосредственно улавливать и поглощать СР, что приводит к устранению и уменьшению клеточных нарушений [20].…”
Section: оксидативный стресс: основные патофизиологические звеньяunclassified
See 2 more Smart Citations
“…Studies conducted on male C57BL/6 mice in whom hyperglycemia was induced with streptozotocin showed an increase in MDA and a decrease in total antioxidant capacity (TAC), SOD total, SOD2 (Mn-dependent SOD), and the GSH/GSSG (glutathione disulfide) ratio in the endothelium [67]. Cohort studies conducted in a group of 382 diabetic children reported reduced serum GPX, SOD, and CAT levels in comparison with healthy children [68]. Similarly, in a study conducted by Varvarovská et al [69,70], reduced levels of antioxidant parameters (SOD, GSH, TAC) and increased MDA were detected in 50 children with type 1 diabetes compared to healthy children.…”
Section: Oxidative Stressmentioning
confidence: 99%